Predicting pragmatic functions of Chinese echo questions using prosody: evidence from acoustic analysis and data modeling - Cao, Siyi; Xu, Yizhong; Zhou, Tongquan; Wu, Anqi (Frontiers in Psychology, 2024)
Echo questions serve two pragmatic functions (recapitulatory and explicatory) and has two types (yes-no echo question and wh-echo question) in verbal communication. Yet to date, most relevant studies have been conducted in European languages like English and Spanish. It remains unknown whether the different functions of echo questions can be conveyed via prosody in spoken Chinese. Additionally, no comparison was made on the diversified algorithmic models in predicting functions by prosodic cues by Chinese echo questions, a novel linguistic cognition in nature. This motivated us to use different acoustic cues to predict different pragmatic functions of Chinese echo questions by virtue of acoustic experiment and data modeling. The results showed that for yes-no echo question, explicatory function exhibited higher pitch and intensity patterns than recapitulatory function whereas for wh-echo question, recapitulatory function demonstrated higher pitch and intensity patterns than explicatory function. Besides, the algorithm Support Vector Machine (SVM) , compared with Random Forest (RF) and Logistic Regression (LR), performed better when predicting different functions using prosodic cues in both yes-no and wh-echo questions. This study from a digitized perspective adds evidence to the cognition of echo questions' functions on a prosodic basis.